2018
DOI: 10.1542/peds.2017-0635
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Preterm Infants With Postnatal Cytomegalovirus Infection

Abstract: In this cohort study, postnatal cytomegalovirus infection in preterm children did not have an adverse effect on neurodevelopment within the first 6 years of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 36 publications
1
53
1
2
Order By: Relevance
“…In a few studies on postnatal CMV infection other authors found postnatal CMV infection associated with BPD [14,20] suspecting a direct or indirect effect of the virus on the lung tissue [14]. These findings remain conflicting, since other authors could not find an association of BPD and CMV [5]. We further observed increased rates of surgery requiring ROP, but could not find an association of ROP and antiviral therapy in our logistic regression analysis.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In a few studies on postnatal CMV infection other authors found postnatal CMV infection associated with BPD [14,20] suspecting a direct or indirect effect of the virus on the lung tissue [14]. These findings remain conflicting, since other authors could not find an association of BPD and CMV [5]. We further observed increased rates of surgery requiring ROP, but could not find an association of ROP and antiviral therapy in our logistic regression analysis.…”
Section: Discussioncontrasting
confidence: 66%
“…Transmission occurs via untreated breast milk [6]. Most commonly associated symptoms are respiratory decompensation and thrombocytopenia [20] and infection seems to have an effect on respiratory long-term morbidity [14,20], but no effect on neurological long-term outcome [5].…”
Section: Introductionmentioning
confidence: 99%
“…Neurodevelopmental assessment to the age of 6 years was performed in 49 infected infants, with no difference in the first 3 years of life identified. Although pCMV-infected children had significantly lower verbal IQ scores at the age of 6 years, multiple regression analysis indicated no impact of CMV status but significant influence of maternal education and ethnicity 31. A single-centre, case-controlled study in 19 CMV-infected infants showed subtle, in parts statistically significant, differences in motor and cognitive outcomes 35.…”
Section: Clinical Presentationmentioning
confidence: 91%
“…Multiple population-based cohort studies have shown no association between pCMV infection and sensorineural hearing loss 31–33…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Regarding the debate over the long-term cognitive consequences of postnatal CMV infection through human milk in preterm infants, a recent large prospective study conducted in the Netherlands involving 356 preterm infants with a gestational age of <32 weeks followed-up until age 6 years reported that neurodevelopmental problems, including hearing loss, are unlikely ( 47 ). As pasteurization or freezing reduces the biological and immunological protective value of breastmilk against necrotizing enterocolitis ( 48 ), the study concluded that these processes may not be justified ( 47 ).…”
Section: Maternal Infectionsmentioning
confidence: 99%